2013
DOI: 10.1111/roiw.12030
|View full text |Cite
|
Sign up to set email alerts
|

Country Differences in Material Deprivation inEurope

Abstract: This paper assesses to what extent differences in the characteristics of individuals (micro‐level perspective) and country‐specific factors (macro‐level perspective) can explain country differences with respect to material deprivation levels. Thus, our work aims to simultaneously consider the macro dimension and the predominantly individually‐oriented study field of material deprivation using multilevel techniques. We make use of the European Union Statistics on Income and Living Conditions. Our results show t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 48 publications
(94 reference statements)
6
52
0
Order By: Relevance
“…It is interesting to note that the elderly have in 2012 a lower probability than non-elderly adults of combining low income and material deprivation, whether living alone or as part of a couple. This is coherent with results from other studies showing that in Spain, as well as in other countries, elderly people do not only show comparatively low material deprivation levels (Bárcena-Martín et al, 2014), but also are the age group least affected by the crisis, probably due to their lower exposure to recent fluctuations in labour and property markets.…”
Section: Outright Ownersupporting
confidence: 81%
See 1 more Smart Citation
“…It is interesting to note that the elderly have in 2012 a lower probability than non-elderly adults of combining low income and material deprivation, whether living alone or as part of a couple. This is coherent with results from other studies showing that in Spain, as well as in other countries, elderly people do not only show comparatively low material deprivation levels (Bárcena-Martín et al, 2014), but also are the age group least affected by the crisis, probably due to their lower exposure to recent fluctuations in labour and property markets.…”
Section: Outright Ownersupporting
confidence: 81%
“…In Spain, it has been shown that the 82 rosa martínez and carolina navarro poverty map varies when account is taken of the regional differences in the cost of living (Ayala, Jurado and Pérez-Mayo, 2014). Poor health status, the number of dependent children or lone parenthood also tend to increase the risk of material deprivation, even after controlling for the «adjusted» income level of the household (Bárcena-Martín et al, 2014;Fusco, Guio and Marlier, 2011;Dewilde, 2008;Ayllón, Mercader and Ramos, 2007;Layte et al, 2001). A relative robust finding is the existence of a reverse relationship between age and material deprivation, with the elderly being much less deprived than expected according to their income levels (Figari, 2012;Muffels and Fouarge, 2004;Whelan, Maître and Nolan, 2007, among others).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Typically, poor health and disability, economic inactivity and low education are related to higher risks of material poverty (Bárcena‐Martín et al . ; Boarini and d'Ercole ; Brady et al . ; Kim et al .…”
Section: Theoretical and Empirical Considerationsmentioning
confidence: 99%
“…Only a few scholars have examined whether and how the social policy context of a country is associated with individual material deprivation (Nelson ; Bárcena‐Martín et al . ). Additionally, there is a lack of multi‐level studies that address both material deprivation and income poverty, and that acknowledge the interaction between social protection arrangements and ill‐health as well as social position.…”
Section: Introductionmentioning
confidence: 97%
“…Layte et al, 2001or Bárcena-Martin et al, 2014. One of the limitations of cross-sectional analysis is that it does not allow controlling for unobserved factors such as social networks or skills that might affect the relationship under study.…”
Section: Introductionmentioning
confidence: 98%